Adsorption of cationized eucalyptus heteropolysaccharides onto chemical and mechanical pulp fibers. (5th June 2015) - Hu, Guichun; Fu, Shiyu; Liu, Hao; Lucia, Lucian A.
Highlights: The native heteropolysaccharides isolated from eucalyptus wood was adsorbed on bleached softwood and hardwood kraft pulps and mechanical pulp. The eucalyptus heteropolysaccharides preferred to adsorb on bleached kraft pulps compared to bleached mechanical pulp. The heteropolysaccharides with low arabinose content were preferentially adsorbed onto the hardwood fibers. The cationized heteropolysaccharides significantly increased the adsorption on pulp fibers. Abstract: Adsorption of native eucalyptus heteropolysaccharides onto bleached softwood and hardwood kraft pulps and bleached CTMP was explored in this work to potentially improve the mechanical properties of the final furnish. It was found that adsorption of native heteropolysaccharides onto softwood kraft pulp was slightly higher than hardwood; however, heteropolysaccharides with low arabinose content were preferentially adsorbed onto the hardwood fibers. Adsorption onto CTMP was the lowest, although the general phenomenon of native absorption was rather low under the applied conditions. A strategy to increase the absorption required cationizing the heteropolysaccharides with 2, 3-epoxy propyltrimethylamonium chloride that in general significantly increased the overall phenomenon, again with the same general tendencies as observed for the native adsorption.